2013
DOI: 10.6061/clinics/2013(07)04
|View full text |Cite
|
Sign up to set email alerts
|

Myositis-specific and myositis-associated autoantibody profiles and their clinical associations in a large series of patients with polymyositis and dermatomyositis

Abstract: OBJECTIVE:To analyze the prevalence of myositis-specific and myositis-associated autoantibodies and their clinical correlations in a large series of patients with dermatomyositis/polymyositis.METHOD:This cross-sectional study enrolled 127 dermatomyositis cases and 95 polymyositis cases. The disease-related autoantibody profiles were determined using a commercially available blood testing kit.RESULTS:The prevalence of myositis-specific autoantibodies in all 222 patients was 34.4%, whereas myositis-associated au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
77
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 33 publications
12
77
1
7
Order By: Relevance
“…A recent Japanese study showed that nailfold punctate hemorrhages are more frequently seen in patients with anti-Mi-2 (89 %) than in patients with anti-melanoma differentiation-associated gene 5 product (MDA5) (37 %) or anti-transcriptional intermediary factor 1 gamma (TIF1γ)/α (44 %) [24]. A recent Brazilian study showed that anti-Mi-2-positive DM patients are significantly more likely to have photosensitivity and the shawl sign by univariate analysis but that, by multivariate analysis, the anti-Mi-2 antibody was associated only with photosensitivity [25]. According to a North American collaborative study, JDM patients with the anti-Mi-2 antibody showed the V-neck sign, the shawl sign, and cuticular overgrowth significantly less than adult DM patients did [26].…”
Section: Anti-mi-2 Antibodymentioning
confidence: 94%
“…A recent Japanese study showed that nailfold punctate hemorrhages are more frequently seen in patients with anti-Mi-2 (89 %) than in patients with anti-melanoma differentiation-associated gene 5 product (MDA5) (37 %) or anti-transcriptional intermediary factor 1 gamma (TIF1γ)/α (44 %) [24]. A recent Brazilian study showed that anti-Mi-2-positive DM patients are significantly more likely to have photosensitivity and the shawl sign by univariate analysis but that, by multivariate analysis, the anti-Mi-2 antibody was associated only with photosensitivity [25]. According to a North American collaborative study, JDM patients with the anti-Mi-2 antibody showed the V-neck sign, the shawl sign, and cuticular overgrowth significantly less than adult DM patients did [26].…”
Section: Anti-mi-2 Antibodymentioning
confidence: 94%
“…Anti-Jo-1 is the most frequent autoantibody associated with ASS, whereas anti-PL-7 accounts for only 5%-10% of cases (4, 5). Anti-SSA 52kD antibodies are found in 5%-15% of patients with IIM and are strongly associated with anti-Jo-1 or other antiaminoacyl-tRNA antibodies (6). Anti-Ku is reported in 2%-23% of patients with IIM, with higher rates being observed in polymyositis-scleroderma overlap syndromes (6-8).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the results was based on the methods established in a previous study. 22 In the case of the anti-MDA-5 autoantibody, identification was performed using the Enzyme-linked immunosorbent assay (ELISA) method, through recombinant MDA-5 and the anti-MDA-5 monoclonal antibody (MyBioSource, CA, USA). Results were evaluated according to methods established in a previous study.…”
Section: Medicalexpress (São Paulo Online) 2018;5:mo18002mentioning
confidence: 99%